COMPOSITION VEGETATION IDENTIFICATION OF MANGROVE IN THE ECOTOURISM AREA OF BANGKOâBANGKO WEST LOMBOK - ., Junaidi (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The Mangrove forest in some areas on the island of Lombok has decreased in both quantity and quality. These problems are mainly caused by factors: excessive exploitation, functional changes, and natural factors. The Natural Park of Bangko-Bangko (Taman Wisata Alam Bangko-Bangko,/TWABB) in Batu Putih village, District of Sekotong West Lombok has been established as a conservation area with the primary purpose for the benefit of tourism and outdoor recreation, which has an area of Â± 50 ha. Lack of accurate and scientific information will result in ineffective management, so the result would damage the existing mangrove ecosystem. The purpose research to find out 1) species of mangroves are present in TWABB? 2) dominate species of mangrove in TWABB? and 3) species the highest Important Value Index of mangroves in TWABB?To identify the mangrove type the researcher used mangrove identification books. For the Diversity Index and the Important Value Index of mangroves in TWABB the researcher utilized the diversity index formulationsÂ The research results showed 12 (twelve) types of mangroves exist. Seedlings total reaches 28,000 stems/ha, 13,760 saplings stems/ha and tree level 445 stems/ha. Rhizophora stylosa has the highest importance value index, and the lowest index occupied by the type of Ceriops decandra